2015
DOI: 10.1016/j.yebeh.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosotomy versus vagus nerve stimulation for atonic seizures and drop attacks: A systematic review

Abstract: Atonic seizures are debilitating and poorly controlled with antiepileptic medications. Two surgical options are primarily used to treat medically refractory atonic seizures: corpus callosotomy (CC) and vagus nerve stimulation (VNS). However, given the uncertainty regarding relative efficacy and surgical complications, the best approach for affected patients is unclear. The PubMed database was queried for all articles describing the treatment of atonic seizures and drop attacks with either corpus callosotomy or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 40 publications
3
49
0
5
Order By: Relevance
“…Callosotomy utilization has decreased since the introduction of VNS, which also helps prevent tonic and atonic seizures, though there is disagreement regarding which intervention has the best efficacy/risk profile for this purpose [139,26,1,108,138]. One recent systematic review suggests that callosotomy may be more effective than VNS in reducing atonic seizure frequency [105]. It has also been proposed that both therapies may be employed together in certain patients with particularly debilitating drop attacks [64].…”
Section: Disconnection Proceduresmentioning
confidence: 99%
“…Callosotomy utilization has decreased since the introduction of VNS, which also helps prevent tonic and atonic seizures, though there is disagreement regarding which intervention has the best efficacy/risk profile for this purpose [139,26,1,108,138]. One recent systematic review suggests that callosotomy may be more effective than VNS in reducing atonic seizure frequency [105]. It has also been proposed that both therapies may be employed together in certain patients with particularly debilitating drop attacks [64].…”
Section: Disconnection Proceduresmentioning
confidence: 99%
“…There are a number of systematic reviews of surgical treatment for refractory epilepsy, but to date only one has focused on corpus callosotomy and one has compared corpus callosotomy to vagus nerve stimulation (VNS) . Hader et al .…”
mentioning
confidence: 99%
“…Generally, complete corpus callosotomy resulted in a greater reduction than partial corpus callosotomy but was associated with an increased risk of permanent disconnection syndrome compared with partial corpus callosotomy. Rolston et al . found that VNS is a reversible alternative to corpus callosotomy with fewer complications, but is less likely to have a clinically significant reduction in drop attacks.…”
mentioning
confidence: 99%
“…9 Compared to other treatment modality, a metaanalysis showed that callosotomy had better rate of seizure freedom and control than vagal nerve stimulation (VNS) for drop attacks. 10 Since earlier age at surgery resulted in better outcomes and lower complications, corpus callosotomy should be performed immediately once the epileptic patient is diagnosed as medically intractable. 11 The average duration from onset to surgery was 8.78±6.69 years, almost comparable with a study from the US (mean 8.4 years).…”
Section: Discussionmentioning
confidence: 99%